Analisis Pengendalian Persediaan Pada Beras Bulog (Studi Kasus Perum Bulog Cabang Bukittinggi) - Hanna Filjanah; Melia Handayani; Wenny Ananda Larasati (CV. ITTC INDONESIA, 2026)
Inventory control is an important aspect in maintaining stock availability and operational cost efficiency within a company. At Perum BULOG Bukittinggi Branch, the ordering policy for commercial rice has not been fully optimized, which has the potential to increase total inventory costs. This study aims to determine the optimal order quantity, safety stock, reorder point, and total inventory cost using the Economic Order Quantity (EOQ) method. The research employs a quantitative approach with a descriptive research design. The population of this study consists of commercial rice inventory data at Perum BULOG Bukittinggi Branch, while the sample includes annual demand data, ordering costs, holding costs, and the company’s lead time. Data collection techniques were carried out through documentation and literature study, while data analysis was conducted using the EOQ method. The results show that the optimal order quantity is 1,543 units with an ordering frequency of 7–8 times per year. The application of the EOQ method reduces the total inventory cost from Rp33,500,374 to Rp30,199,932, resulting in a cost efficiency of Rp3,300,441 per year. The calculated safety stock is 359 units and the reorder point is 585 units. The implementation of the EOQ method can improve cost efficiency and make the inventory control system more measurable and systematic at Perum BULOG Bukittinggi Branch..